Pengaruh Struktur Modal, Ukuran Perusahaan, Profitabilitas Terhadap Nilai Perusahaan Non Manufaktur Tahun 2020-2024: Penelitian - Mila Hayati; Rina Malahayati; Dicky Zulkarnaen (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Company Value is one of the most important factors for investors and creditors in deciding whether to invest, and creditors will use Company Value as a factor in deciding whether to provide loans. The purpose of this study is to determine and analyze the Effect of Capital Structure, Company Size, Profitability on the Value of Non-Manufacturing Companies in 2020-2024. The type of data used in this study is quantitative data with secondary data sources, namely from company financial reports. The collected data were tested using SPSS software consisting of descriptive statistical tests, classical assumption tests, multiple linear regression, and simultaneous and partial hypothesis tests and coefficients of determination. The results of the study indicate that capital structure has a partial positive and significant effect on company value. This shows that capital structure has a theoretical and real effect in increasing company value in non-manufacturing companies in the plantation sector for the period 2020-2024. Company size has a partial positive and significant effect on company value. This shows that company size has a theoretical and real effect in increasing company value. Profitability partially has a negative and insignificant effect on company value in non-manufacturing companies in the plantation sector for the period 2020-2024. This shows that profitability does not have a significant effect in increasing the company value of non-manufacturing companies in the plantation sector for the period 2020-2024. Capital structure, company size and profitability simultaneously have a positive and significant effect on company value in non-manufacturing companies in the plantation sector for the period 2020-2024. In the coefficient of determination, the Adjusted R2 value obtained is 0.15, meaning that variations in the variables Capital structure, company size and profitability can explain their influence on company value by 15% while the remaining 75% is a variation in other variables not explained in this study, for example cash flow, etc.